Effect of Preoperative Parameters on Outcomes of Lumbar Microdiscectomy: A Retrospective Analysis - Mehendiratta, Dhanish; Patel, Pratik; Bhambhu, Vivek; Chaudhary, Kshitij; Dalvie, Samir (Asian Journal of Neurosurgery, 2022)
Objective The objective of this study was to characterize the effect of preoperative variables on outcomes after minimally invasive lumbar microdiscectomy.Materials and Methods This study was done from January 2019 to May 2020. This included medical records of all patients who were diagnosed with lumbar disc herniation and treated surgically by microdiscectomy. The medical records of such patients from January 2016 to January 2018 were included in this study. Postoperative outcomes were analyzed by Oswestry Disability Index (ODI), visual analog scale (VAS) leg, and VAS back scores, that were noted at preoperative, immediate postoperative, 6 months postoperative, and 1 year after operation. Difference in each outcomes score was calculated postoperatively with respect to the preoperative readings. Minimal clinically important difference was further calculated for each outcome score.Results On analyzing the ODI, VAS leg, and VAS back scores across various age groups, genders, body mass indexes, addictions, comorbidities, preoperative epidural steroid injection and physiotherapy, and levels of disc herniation, and it was found that there was no statistically significant difference across these categories. However, the ODI scores (∼ ODI) at all time points showed greater difference in the younger age group, that is, 18 to 30 years, males, nonsmokers, those with symptom duration of less than 6 weeks, and with disc herniation at L3 to L4.Conclusion The findings of this study will help to properly counsel patients with regard to the factors mentioned above so as to set realistic expectations, to help improve the outcomes, and for appropriate surgical decision making, that is, at which point should a surgical intervention be made.
Keywords: preoperative; lumbar microdiscectomy; ODI; VAS; MCID